2017
DOI: 10.1111/idj.12275
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up assessment of problem-based learning in dental alveolar surgery education: a pilot trial

Abstract: The PBL mode of teaching integrated dental alveolar surgery may improve preparedness for clinical practice and help undergraduates to develop the desire to collaborate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Twenty‐two RCTs involving 1969 participants were included (Bai et al, 2017; Bukumiric et al, 2022; Cong et al, 2017; Dyke et al, 2001; Faisal et al, 2016; Jamshidi et al, 2021; Khatiban et al, 2019; Khatiban & Sangestani, 2014; Kim, 2019; Kim & Shin, 2014, 2016; Lee & Son, 2022; Li et al, 2020; Lian & He, 2013; Lin et al, 2010; Lohse et al, 2003; Peng et al, 2021; Pourshanazari et al, 2013; Smits et al, 2003; Sun & Qi, 2017; Wu et al, 2020; Zhao & Cong, 2019). The numbers of participants in the experimental and control groups were 1003 and 966, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐two RCTs involving 1969 participants were included (Bai et al, 2017; Bukumiric et al, 2022; Cong et al, 2017; Dyke et al, 2001; Faisal et al, 2016; Jamshidi et al, 2021; Khatiban et al, 2019; Khatiban & Sangestani, 2014; Kim, 2019; Kim & Shin, 2014, 2016; Lee & Son, 2022; Li et al, 2020; Lian & He, 2013; Lin et al, 2010; Lohse et al, 2003; Peng et al, 2021; Pourshanazari et al, 2013; Smits et al, 2003; Sun & Qi, 2017; Wu et al, 2020; Zhao & Cong, 2019). The numbers of participants in the experimental and control groups were 1003 and 966, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the performance outcomes were objective assessments from tutors or supervisors. Fifteen studies reported analyzable outcomes of performance for the meta‐analysis (Bai et al, 2017; Bukumiric et al, 2022; Cong et al, 2017; Jamshidi et al, 2021; Khatiban et al, 2019; Khatiban & Sangestani, 2014; Kim & Shin, 2014; Lee & Son, 2022; Li et al, 2020; Lin et al, 2010; Peng et al, 2021; Smits et al, 2003; Sun & Qi, 2017; Wu et al, 2020; Zhao & Cong, 2019), among which all 15 reported post‐interventional performance scores, and seven also reported performance scores before interventions (Jamshidi et al, 2021; Khatiban et al, 2019; Kim & Shin, 2014; Lee & Son, 2022; Lin et al, 2010; Smits et al, 2003; Sun & Qi, 2017; Wu et al, 2020; Table 2). The maximum score ranged from 3 to 100.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maskur (2020) found that PBL helped students with research skills by enabling them to benefit from different sources of information. Similarly, Bai et al (2017) and Naimnule et al (2020) considered PBL as a method that provides students with research skills. Kardipah and Wibawa (2020) emphasized that students learned to use time effectively, in other words, they gained time management skills, depending on the multi-stage structure of PBL.…”
Section: Conclusion and Discussionmentioning
confidence: 99%